2013
DOI: 10.1159/000339810
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove and Peat Swamp Forests: Refuge Habitats for Primates and Felids

Abstract: Swamp forests may be important refuges for primates and felids where these taxa are threatened with habitat loss. Mangrove and peat swamp forests, impenetrable, wet habitats, inaccessible and uninhabitable for humans, may, in some regions, be the most significant remaining habitats for threatened species. They are nevertheless neglected in field studies compared to relatively species-rich, terrestrial tropical forests probably, in part, because of the difficulties associated with surveying them. As a result, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…This finding underscores the view that the emphasis on mangroves as marine ecosystems has led to the importance of the terrestrial components of mangrove forests being undervalued (Luther & Greenberg, 2009;Nowak, 2013). In addition to extending our knowledge of the global richness of terrestrial vertebrates in mangrove ecosystems, our results also reveal a wider range of countries in which these species use mangroves than previously reported (Figure 1b, c).…”
Section: Species Distribution and Richnesssupporting
confidence: 83%
See 2 more Smart Citations
“…This finding underscores the view that the emphasis on mangroves as marine ecosystems has led to the importance of the terrestrial components of mangrove forests being undervalued (Luther & Greenberg, 2009;Nowak, 2013). In addition to extending our knowledge of the global richness of terrestrial vertebrates in mangrove ecosystems, our results also reveal a wider range of countries in which these species use mangroves than previously reported (Figure 1b, c).…”
Section: Species Distribution and Richnesssupporting
confidence: 83%
“…We found mangrove forests to be substantially more important for terrestrial vertebrates than previously reported, supporting a remarkable richness of terrestrial mammals, reptiles and amphibians globally. This finding underscores the view that the emphasis on mangroves as marine ecosystems has led to the importance of the terrestrial components of mangrove forests being undervalued (Luther & Greenberg, 2009;Nowak, 2013).…”
Section: Species Distribution and Richnessmentioning
confidence: 55%
See 1 more Smart Citation
“…Peat swamps regulate hydrology by mitigating floods during wet seasons and intense rainfall events, and maintain base flows in streams and rivers during dry periods by slowly releasing stored water. Peat forests are also high in biodiversity and are critical habitat for many rare and endangered species including Sumatran tigers, orangutans, gibbons, and leopards [1720]. Despite these values, Indonesian peat swamp forests are being deforested, drained and converted at unprecedented rates [2123].…”
Section: Introductionmentioning
confidence: 99%
“…Chimpanzees (Pan troglodytes) for example, are often categorised by their forest behaviour, although their behaviour in savannah habitats differs greatly [1]. A study from 2013 reported many felids and primates using mangrove and peat swamp forest, yet most research conducted on them focused on their behavioural ecology in forests [2]. For other species, such as the leopard (Panthera pardus), research has focused on its behaviour in savannah areas, even though this behaviour is substantially different in forests [3].…”
Section: Introductionmentioning
confidence: 99%